Unraveling the mechanism of biomimetic hydrogen fuel production – a first principles molecular dynamics study. Issue 19 (18th March 2020) - Puthenkalathil, Rakesh C.; Etinski, Mihajlo; Ensing, Bernd
Abstract : The Fe2 (bdt)(CO)6 [bdt = benzenedithiolato] complex, a synthetic mimic of the [FeFe] hydrogenase enzyme can electrochemically convert protons into molecular hydrogen. The free energy landscape reveals a different mechanism for the biomimetic cycle. Abstract : The Fe2 (bdt)(CO)6 [bdt = benzenedithiolato] complex, a synthetic mimic of the [FeFe] hydrogenase enzyme can electrochemically convert protons into molecular hydrogen. Molecular understanding of the cascade of reaction steps is important for the design of more efficient catalysts. In this study, we investigate the reaction mechanism of the hydrogen production catalysis in explicit solution of acetonitrile using first principles molecular dynamics simulations. We have characterized all reduction and protonation intermediates taking part in the catalytic cycle. Free energy surfaces of the activated reaction steps are calculated using metadynamics. We find that the second protonation leading to molecular hydrogen formation is the rate limiting step. Direct protonation of the bridging hydride by a proton from the solution to form H2 is the most favorable reaction pathway. However, also a bdt sulfur atom can become protonated, leading to a possible proton trap state that reduces the catalytic efficiency. Our calculations validate the ECEC mechanism proposed using cyclic voltammetry.